HTLV-1 persistence and leukemogenesis: A game of hide-and-seek with the host immune system - Tan, Benjy J. Y.; Sugata, Kenji; Ono, Masahiro; Satou, Yorifumi (Frontiers in Immunology, 2022)
Human T-cell leukemia virus type 1 (HTLV-1), a retrovirus which mainly infects CD4+ T cells and causes adult T-cell leukemia/lymphoma (ATL), is primarily transmitted via direct cell-to-cell transmission. This feature generates a wide variety of infected clones in hosts, which are maintained via clonal proliferation, resulting in the persistence and survival of the virus. The maintenance of the pool of infected cells is achieved by sculpting the immunophenotype of infected cells and modulating host immune responses to avoid immune surveillance. Here, we review the processes undertaken by HTLV-1 to modulate and subvert host immune responses which contributes to viral persistence and development of ATL.